Penerapan Metode Enhanced Phytoremediation pada Lahan Bekas Tambang Emas Desa Tirta Kencana Kecamatan Bengkayang - Khairunnisa, Aulia; Sulastri, Aini; Jumiati, Jumiati (Universitas Tanjungpura, 2024)
Community gold mining activities using the amalgamation method cause soil pollution due to the use of mercury (Hg) to extract gold content which causes a decrease in soil quality and environmental damage. Enhanced phytoremediation is a method that can be applied to remove mercury levels with using the Cyperus kyllingia plant and adding supporting elements in the form of bacterial isolates that are resistant to mercury. This research aimed to determine the effectiveness of Cyperus kyllingia plants and bacterial isolates for removing mercury levels in mercury-contaminated soil, as well as observing the bacterial population and plant morphology during the research. Based on the research results, it is known that the best efficiency value for removing mercury levels is found in phytoremediation with the addition of bacterial isolates, namely 86.88%. The largest bacterial population was found in the phytoremediation reactor with the addition of bacterial isolates, namely 73.3 Ã— 106 CFU/mL. The mercury content in polluted soil causes changes in plant morphology, namely the color of green plants changes to yellow, but plants can reproduce as indicated by an increase in the number of leaves and plant stems